Reversal of ergotamine-induced vasospasm following methylprednisolone - Rahman, Ali; Yildiz, Mustafa; Dadas, Erdogan; Donder, Emir; Cihangiroglu, Mutlu; Eken, Cenker; Bozdemir, M. Nuri (Taylor & Francis Ltd, 2008)
Introduction. Ergotamine, an ergot alkaloid with partial agonist effects on alpha 1 receptors and serotonin receptors, is widely used in the treatment of migraine. Ergotamine may cause severe vasospasm. Case report. A 25-year-old man was admitted to the emergency department with complaints Of Sudden coldness, pallor, and pain in his hands and feet for 2 days. He had been using a drug containing ergotamine for his migraine headaches for 1 week. On examination, the pulses of the radial, ulnar, popliteal, and tibial arteries were bilaterally undetectable. Treatment consisted of sodium nitroprusside and heparin. On the third day of the admission, bilateral brachial and femoral artery pulses were lost and his complaints exacerbated. Angiography revealed diffuse vasospasm of the arteries in the both lower 14 extremities (Fig. 1A and C). Because of the lack of response to the ongoing therapy, a single dose of methylprednisolone sodium succinate (1 mg/kg) was given intravenously; the nitroprusside infusion was terminated because of the development of hypotension. The pulses were palpable 2 h after the methylprednisolone dose. Angiography done 12 h after the methylprednisolone dose showed improvement of the 4 vasospasm in the lower extremities. Recovery was uneventful and follow-up evaluation found no abnormalities. Discussion. Although vasodilator agents are first-line therapy in the treatment of ergotism, corticosteroids may be considered as an alternative therapy, especially for intractable cases. The mechanism by which corticosteroids dilate arteries is not clear. Conclusions. Ischemia in an extremity secondary to ergotamine-induced vasospasm unresponsive to sodium nitroprusside may be treated successfully with methylprednisolone.
Keywords: Ergotamine; Ergotism; Arterial vasoconstriction; Methylprednisolone